Optimized detection of lung IL-6 via enzymatic liquefaction of low respiratory tract samples: application for managing ventilated patients. Issue 21 (28th September 2021) - Clemente, Antonio; Alba-Patiño, Alejandra; Santopolo, Giulia; Barón, Enrique; Rojo-Molinero, Estrella; Oliver, Antonio; Pérez-Bárcena, Jon; Merino de Cos, Paz; Aranda, María; del Castillo, Alberto; Socias, Antonia; Borges, Marcio; et al.
Abstract : IL-6 immunodetection in respiratory samples is boosted using an enzymatic method for liquefying samples prior to analysis. This increases the predictive power of lung IL-6 as a biomarker of respiratory function. Abstract : Lung IL-6 is a promising biomarker for predicting respiratory failure during pulmonary infections. This biomarker is found in respiratory samples which need to be liquefied prior to analysis. Traditional liquefying methods use reducing agents such as dithiothreitol (DTT). However, DTT impairs immunodetection and does not liquefy highly viscous samples. We propose an enzymatic method that liquefies samples by means of generating O2 bubbles with endogenous catalase. Low respiratory tract specimens from 48 mechanically ventilated patients (38 with SARS-CoV-2 infection) were treated with DTT or with the enzymatic method. We used turbidimetry to compare the liquefaction degree and IL-6 was quantified with ELISA. Finally, we used AUC-ROC, time-to-event and principal component analysis to evaluate the association between respiratory compromise or local inflammation and IL-6 determined with both methods. Enzymatically treated samples were better liquefied than those reduced by DTT, which resulted in higher ELISA signals. Lung IL-6 levels obtained with the enzymatic procedure were negatively correlated with the oxygenation index (PaO2 /FiO2 ) and the time of mechanical ventilation. The proposed enzymatic liquefaction method improves the sensitivity for lung IL-6 detection in respiratory samples, which increases its predictive power as a biomarker for evaluating respiratory compliance.